Extraction of Silicon-Containing Nanoparticles from an Agricultural Soil for Analysis by Single Particle Sector Field and Time-of-Flight Inductively Coupled Plasma Mass Spectrometry - Zhizhong Li; Madjid Hadioui; Kevin J. Wilkinson (Nanomaterials, 2023)
The increased use of silica and silicon-containing nanoparticles (Si-NP) in agricultural applications has stimulated interest in determining their potential migration in the environment and their uptake by living organisms. Understanding the fate and behavior of Si-NPs will require their accurate analysis and characterization in very complex environmental matrices. In this study, we investigated Si-NP analysis in soil using single-particle ICP-MS. A magnetic sector instrument was operated at medium resolution to overcome the impact of polyatomic interferences (e.g., 14N14N and 12C16O) on 28Si determinations. Consequently, a size detection limit of 29 ± 3 nm (diameter of spherical SiO2 NP) was achieved in Milli-Q water. Si-NP were extracted from agricultural soil using several extractants, including Ca(NO3)2, Mg(NO3)2, BaCl2, NaNO3, Na4P2O7, fulvic acid (FA) and Na2H2EDTA. The best extraction efficiency was found for Na4P2O7, for which the size distribution of Si-NP in the leachates was well preserved for at least one month. On the other hand, Ca(NO3)2, Mg(NO3)2 and BaCl2 were relatively less effective and generally led to particle agglomeration. A time-of-flight ICP-MS was also used to examine the nature of the extracted Si-NP on a single-particle basis. Aluminosilicates accounted for the greatest number of extracted NP (~46%), followed by NP where Si was the only detected metal (presumably SiO2, ~30%).